Record of the subgenus, Gryllitara Chopard, 1931 (Orthoptera: Gryllidae: Itarinae) and description of a new species from India - Meena, Ashok Kumar; Swaminathan, Rajamani; Nagar, Rajendra; Chhangani, Gaurang; Kumar, Kuldeep (Zootaxa, 2021)
In the present paper, we report the occurrence of the cricket subgenus Gryllitara Chopard, 1931 from India along with the description of a new species, Itara (Gryllitara) pilosa sp. nov., from the state of Kerala, South India. Suitable plates with close-up details have been presented to describe the new species, as well as for Itara (Itara) vietnamensis Gorochov being reported from North East India.